Pseudotumoral tuberculous ureteritis: a case report - Bouchikhi, Ahmed-Amine (BioMed Central, 2013)
INTRODUCTION: Tuberculosis is still endemic in Morocco and the urogenital form is common. This form is characterized by clinical polymorphism. However, the isolated ureteric form is very rare. The differential diagnosis might be raised in tumoral cases while undertaking surgical excision which is the realistic choice. Hence, we report an isolated ureteric tuberculosis case, and we discuss the clinical, imaging, diagnostic and therapeutical features. CASE PRESENTATION: A 30-year-old Moroccan man consulted us for left back pain associated with urinary frequency and a few macroscopic episodes of hematuria for the past six months. A computed tomography urography revealed a left hydronephrosis and hydroureter secondary to focal wall thickening of the left lumbar ureter. Hence, we had diagnosed a ureteral tumor. However, a clinical examination showed irritative voiding symptoms and epididymal disorders associated with prostate infection suggesting a Koch’s bacillus assessment of the patient’s urine of which the results proved strongly positive. The treatment consisted of establishing a double-J ureteric stent to drain the left kidney, followed by antituberculous antibiotics. CONCLUSION: Urogenital tuberculosis is common in endemic countries, however isolated ureter affection is rare. It is important to consider a ureteral tuberculosis diagnosis whenever ureteral thickening is revealed in a patient living in a country in which tuberculosis is endemic.